2020
DOI: 10.1080/23738871.2020.1740753
|View full text |Cite
|
Sign up to set email alerts
|

The influence of internet architecture on centralised versus distributed internet services

Abstract: The internet evolves rapidly as innovations in technology, applications and business emerge. In some cases, the changes have also given rise to the creation of centralised service deployment models and industry consolidation. This paper focuses on the question of how internet technology and open interfaces may affect the ability to deploy services in a collaborative fashion vs in a centralised fashion. The paper presents a categorisation of factors influencing these choices and discusses these factors in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Inés M. González Vidal & Adriana Gewerc Barujel. Página 4 de 24 causing the network effect 2 that increases the value of the service 3 and can lead to an asymmetry of power, which in turn can be reflected in various aspects of the service (Arkko, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Inés M. González Vidal & Adriana Gewerc Barujel. Página 4 de 24 causing the network effect 2 that increases the value of the service 3 and can lead to an asymmetry of power, which in turn can be reflected in various aspects of the service (Arkko, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…It also refers to the consolidation of the Internet through an ecosystem of contemporary digital platform architectures, which exerts greater control over infrastructures and services by a small group of organizations, capable of easily reaching a large user market. In this sense, network effects affect the value of the service and this can lead to an asymmetry of power, which in turn can be re ected in various aspects of people's lives digitally mediated (Arkko, 2020).…”
Section: Objectivementioning
confidence: 99%
“…On the other hand, the change refers to the in uence of these contemporary digital platform architectures that induce a change in the state of people different from the predictable one; In uence can be classi ed as a subjective concept and, as such, the perception of in uence varies by observer (Arkko, 2020;March 1957). Some research suggested that the in uence of contemporary digital architectures will have strong connections with the issues of social justice, equity, equality of results, equal opportunities, social cohesion and human capital (Arkko, 2020;Cinnamon, 2020). In this sense, it will be necessary to increase the study of equity, innovation, the concepts of social, digital and educational exclusion, as well as their opposite category (Anttiroiko & de Jong, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While classic policy making relies on consolidating input from stakeholders and taking interests and capabilities into account, a responsible Internet enables policy makers to take a more data-driven and proactive approach based on network descriptions. For example, a responsible Internet enables national policy makers to: (1) analyze risk areas in their local Internet infrastructure (e.g., concentrations of power or single points of failure [13]) based on historical data analysis; (2) infer models that help them play out realistic what-if scenarios; and (3) develop new regulatory strategies (e.g., to protect Europe's digital sovereignty [2,3]).…”
Section: Policy Makingmentioning
confidence: 99%
“…For instance, a power grid operator may be reluctant to remotely control power lines at field stations over the Internet because it does not know the properties of the chain of network operators responsible for enabling the communication and cannot control them. Another example is that the opaqueness of the Internet infrastructure may lead to concentrations of power going unnoticed, resulting in individuals and businesses becoming overly dependent on large commercial players they have little influence over [13]. Finally, individuals typically do not know if their data passes through network operators they would not trust or that their employer would disallow for certain classified types of work.…”
Section: Origin and Meaning Of "Responsible"mentioning
confidence: 99%